Neuro-fuzzy equalizers for mobile cellular channels - Raveendranathan, K. C. (Boca Raton [Florida] : Taylor & Francis/CRC Press, 2014)
This book introduces the concepts of channel equalizers for cellular channels. Modeling and simulation of wireless channels forms part of the discussion. The book begins with a brief introduction to mobile wireless channels and their equalization. It then gives a detailed discussion on contemporary equalization schemes, with reference to the vast literature in this area. The author carefully brings in the concept of neuro-fuzzy channel equalization and discusses various types. --
1. Introduction -- 2. Overview of mobile channels and equalizers -- 3. Neuro-fuzzy equalizers for cellular channels -- 4. ANFIS-based channel equalizer -- 5. Compensatory neuro-fuzzy filter (CNFF) -- 6. Radial basis function framework -- 7. Modular approach to channel equalization -- 8. OFDM and spatial diversity -- 9. Conclusion.
Keywords: Wireless communication systems; Mobile communication systems; Fuzzy systems; Neural networks (Computer science)